INFORMATION ASSYMETRI, LEVERAGE AND EARNINGS MANAGEMENT (EMPIRICAL STUDY ON MINING COMPANIES LISTED AT INDONESIA STOCK EXCHANGE) - Tetty Lasniroha Sarumpaet; Agatha Rinta Suhardi (JURNAL ILMIAH BISNIS, PASAR MODAL DAN UMKM, 2019)
Earnings management is a management action to use a method of intentional accounting in the preparation of its financial statements with a separate purpose that resulted in misleading information provided to stakeholders. Earnings management is an agency problem. Agency theory implies the occurrence of information asymmetry between agents and principals that can motivate management to make earnings management. Agency problems also occur between management and creditors, this is supported by positive accounting theory which states that leverage is one thing that can motivate management to make earnings management. Based on the explanation, this research aims to find out how the influence of Information Asymmetry and Leverage to Earnings Management at mining company listed in Indonesia’s Stock Exchange (IDX) in 2014-2016 partially and simultaneously. The research method used is descriptive verification. The population of the research are Mining Companies listed in Indonesia Stock Exchange which amounted to 42 and 31 samples were drawn using purposive sampling technique, based on criteria. The unit of analysis is a financial report and uses multiple linear regression analysis at a significance level of 5%, processed with Eviews 8.0 program. The results showed that the average value of information Asymmetry, Leverage and Earnings Management at mining companies in 2014-2016 showed different changes. Partially Information Asymmetry variable proxied by SPREAD has a positive influence on Earnings Management, whereas, the Leverage variable which is proxied by DAR has negative influence to Earnings Management. Simultaneously, the Asymmetry of Information and Leverage variables affect the Earnings Management.